Sikeres harmadik missziós tevékenység a PTE Kultúratudományi, Pedagógusképző és Vidékfejlesztési Karán - Koltai, Zoltán (Kultúratudományi Szemle, 2024)
Successful third mission activity at the Faculty of Cultural Sciences, Education and Regional Development of UP The essential social functions are often unavailable to dwellers of small settlements. This is an especially pressing issue in those ageing micro-regions suffering from societal problems where the lack of private cars or the decreasing number of public transport connections will make a full life almost impossible. For these people, the only chance for decreasing the isolation is the village caretaker. Commissioned by the Baranya County Council, training of village and farm caretakers of Baranya and Somogy County was implemented at the Faculty of Cultural Sciences, Education and Regional Development of the University of Pécs first in 2022 and then in 2023. The paper presents the experience of the training that was innovative in the University’s life.